Estimating the size of the Cypriot underground economy - A comparison with European experience - Fethi, Meryem Duygun; Fethi, Sami; Katircioglu, Salih Turan (Emerald Group Publishing Ltd, 2006)
Purpose - To measure the size of underground economy and the amount of tax evasion in Cyprus by employing monetary and non-monetary approaches over the period 1960-2003 and to compare the Cyprus figures with some European experience existing in the literature. Design/methodology/approach - Annual data covering the 1960-2003 period were applied to several approaches for measuring the size of underground economy and the amount of tax evasion in Cyprus. These approaches are: employment discrepancy; simple currency ratio; transaction and currency demand. Findings - On the basis of the results obtained from this study: firstly, in Cyprus the average ratio of the underground economy and tax evasion to official GDP is estimated at 9.41 and 0.31 percent of GDP respectively for the study period, and secondly, in the two time intervals where Cypriots figures are internationally comparable with the often quoted EU underground economy figures, the figures for Cyprus are estimated as 5.96 percent of GDP in 1994-95 and 5.67 percent of GDP in 1996-97 whereas the figures for some European Union (EU) members are 18.05 percent of GDP in 1994-95 and 18.76 percent of GDP in 1996-97. Research limitations/implications - Findings of this study suggest that the issue of the underground economy is still in need of further investigation, firstly, to reach reliable results since each approach has its own strengths and weaknesses and yield different results, secondly, to find out the best method selection on a well-established theory, and finally, to employ reliable data estimating measurement. Practical implications - Both EU and Cypriot authorities can utilize this study to analyse the extent of Cypriot underground economy with respect to the other EU members. Such attempts can be useful in developing policies and implementing actions and measures to eliminate underground economy activities. Originality/value - This study is the first of its kind with recent data to measure the size of underground economy and tax evasion for the Cypriot economy by employing various approaches.
Keywords: tax planning; Cyprus